Evaluating Conceptual Framework for Landslides Natural Disaster Management using Feature Analysis - Siswahyudi, Puad; Ramdani, Fatwa; Bachtiar, Fitra A (Journal of Information Technology and Computer Science, 2019)
Landslides is the top rank disaster in the number of incidents in Batu City. Currently, the handling of landslides in Batu City still lack preparation in preparedness phase. In preparedness phase, as an early step before a landslide take place, need a systematic disaster management. The disaster management refers to the use of a framework as a guideline to understand disasters that will occur. Batu City have developed a framework as a guideline for landslide management, but the quality and maturity are questionable. Therefore, this study proposes an evaluation of conceptual framework for landslides natural disaster management. The specific objective is to know the quality of proposed framework, find the weakness and strength. Evaluation is held by using featured based analysis which using seven criteria i.e. background, goal, model, content, legitimation, implementation and contribution. The result shows that the framework Â is feasible to use as a guideline to manage the landslide management in preparedness phase in Batu City.